RHYTHMICS GYMNASTICS: ATHLETES' SELECTION BASED ON SPECIFIC TESTS (Fiep Bulletin - online, 2014)
The main aim of this study was to evaluate rhythmic gymnastics athletes from Manaus, Amazon, aged from six to nineteen years old, and to select those athletes for a high performance training program. The tool used for the evaluation was a specific physical preparation battery test of Rhythmic Gymnastic from Ilia Vankov" (1983). This is comprised by eleven tests, of which only the eight first were applied, the last three were left for the next selection process stage. After this study it is expected to develop a training program that will promote the Rhythmic Gymnastics athletes' evolution within the Amazon state, so that they can achieve the highest performances as compared to the best Brazilian and American athletes, reaching a place in the Brazilian team.
Keywords: evaluation of motor skills; tests; rhythmic gymnastics